Establishing Construct and Concurrent Validity of University of Ibadan Post-UTME on Mathematics Paper (2021)
The study was carried out to establish a construct and concurrent validity test of Post-UTME Mathematics paper for prospective prelim students at university of Ibadan. Two research questions were drawn to guide the establishment of construct and concurrent validity test of Post-UTME Mathematics paper. It is a multiple choice objective test of four options with 100 items. A sample of 358 applicants was randomly drawn to determine the construct and concurrent validity of the test. After item analysis, the result showed that the Post-UTME Mathematics test has a high face and content validity. The test item validity was determined through the grades made in SSCE conducted by either WAEC or NECO, the score obtained in Mathematics by individual candidate in UTME conducted JAMB and the score obtained in Mathematics in Post-UTME conducted by the University of Ibadan. The SSCE results was manipulated by converting A1 = 87.5, B2 = 72, B3 = 67, C4 = 62, C5 = 57, C6 = 52, D7 = 47 and E8 = 42 in percentages to equate SSCE to scores in UTME and PUTME respectively. The test has a construct and concurrent validity coefficient of 0.623 established through the use of Pearson Product Moment Correlation tool. The test is valid and reliable for assessing student‘s ability and capability to gain admission in to university of Ibadan and can be used for selection in to any higher institution in Nigeria.